Meningkatkan Perilaku Menabung UMKM Cikupa dengan Implementasi Strategi Financial Nudging yang Efektif - Munir Nur Komarudin; Dadang Suhardi; Deri Prayudi; Darul Fadli; Dzalika Bunga Azzahra (JAMARI : Jurnal Pengabdian Masyarakat Mandiri, 2026)
This community service activity aims to test the effectiveness of the implementation of the Financial Nudging strategy in improving savings behavior among Micro, Small, and Medium Enterprises (MSMEs) in Cikupa Village, Darma Kuningan. The local MSME community often faces challenges of undisciplined cash management and high financial vulnerability, which are key issues relevant to the sustainability of their businesses. The method used is a behavior-based intervention with a direct survey approach, involving a series of subtle "nudges", such as visual goal setting, savings commitment forms, and default settings for fund allocation. Based on the results of the program evaluation, it shows that the Financial Nudging intervention is able to significantly increase the frequency and amount of funds allocated by MSMEs for savings. In conclusion, Financial Nudging has proven to be a practical, low-cost, and sustainable solution. Its positive impacts are the creation of better financial discipline, reduced dependence on informal loans, and increased financial resilience of MSMEs, which ultimately contribute to the economic stability and welfare of the Cikupa Village community.